Development of GEM (Go Explore Malang) to Enhance Understanding of Natural Tourism Potential in Board Game Based Social Studies Learning - Efendi, Bintang Muhammad Sahara; Wati, Arista; Pratama, Bima Wahyu; Mutia, Tuti; Prasad, Ravinesh Rohit (Jurnal Riset dan Inovasi Pembelajaran, 2025)
This study aims to develop an innovative learning medium called GEM (Go Explore Malang), a board game designed to enhance students’ understanding of natural tourism potential in the Greater Malang area. The research seeks to improve contextual and engaging Social Studies learning by integrating local content with a game-based approach. The development employed the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The product was validated by material and media experts and tested on sixteen ninth-grade students at SMP Negeri 13 Malang. Data were collected using expert validation sheets, student response questionnaires, and learning achievement tests, and analyzed using descriptive statistics. The validation results indicated that GEM achieved 95.71% feasibility from material experts and 81.33% from media experts, categorized as “highly feasible.” Field implementation showed active student participation, increased motivation, and a perfect learning mastery rate. The game effectively enhanced geographical literacy, collaboration, and critical thinking skills through enjoyable play-based interaction. The study was limited to a small sample from one school; future research should expand the testing scope and explore digital adaptations of GEM for wider implementation. GEM can be used as an alternative learning medium that contextualizes Social Studies content, strengthens local awareness, and promotes 21st-century competencies such as collaboration and problem-solving. This research introduces a novel integration of local tourism content into a board game framework, providing a “glocal” innovation that bridges local identity with global learning strategies in Social Studies education.pertama.